Cultural Concerns in the New Journey of Chinese Medical Ethics - Ruiping FAN; Rui DENG (Yixue yu zhexue)
Medical ethics is closely intertwined with culture, and the development of Chinese medical ethics cannot be separated from the concerns of Chinese culture. The internationally popular principlism theory contains misconceptions because it overemphasizes regulative principles while neglecting constitutive principles. It lacks critical reflective equilibrium between the regulative and constitutive principles embedded in specific cultures, and it overlooks the mutual learning and adaptation of constitutive principles across cultures. It is the constitutive principles within various cultures that create new social realities, as they form the values and lifestyles of a culture, thereby giving each specific culture its uniqueness. Cultures should learn from one another's constitutive principles, as these can provide substantial content for explaining, refining, and implementing important regulative principles. The methodological approach of the new journey of Chinese medical ethics lies in achieving a reflective equilibrium between regulative principles and constitutive principles.